2011
DOI: 10.1088/2041-8205/727/2/l27
|View full text |Cite
|
Sign up to set email alerts
|

Non-Racemic Amino Acid Production by Ultraviolet Irradiation of Achiral Interstellar Ice Analogs With Circularly Polarized Light

Abstract: The delivery of organic matter to the primitive Earth via comets and meteorites has long been hypothesized to be an important source for prebiotic compounds such as amino acids or their chemical precursors that contributed to the development of prebiotic chemistry leading, on Earth, to the emergence of life. Photochemistry of inter/ circumstellar ices around protostellar objects is a potential process leading to complex organic species, although difficult to establish from limited infrared observations only. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 40 publications
3
143
0
3
Order By: Relevance
“…As well known, even primitive meteorites have known an episode of thermal and aqueous metamorphism so that a study of its effect on original and genuine organics obtained from photochemical reactions as described above may also be considered and can be easily simulated in non-directed experiments similar to the ones related to extraterrestrial ices evolution. Recently, it has been reported that irradiation of ice analogs using Circularly Polarized UV light on the DESIRS beamline on the synchrotron radiation facility SOLEIL in France, has produced a proteic amino acid, alanine, with a slight but significant enantiomeric excess, similar to the ones observed in some primitive chondrites from the solar nebula [31]. In the framework of a plausible astrophysical scenario, it is then proposed that a direct link between organic materials from primitive chondrites with photochemistry of interstellar ices exists, including a possible photochemistry step using some CPL whose existence in regions of high mass star formation regions is now documented [32].…”
Section: Relevance Of Organic Residues To the Problem Of Prebiotic Mamentioning
confidence: 72%
“…As well known, even primitive meteorites have known an episode of thermal and aqueous metamorphism so that a study of its effect on original and genuine organics obtained from photochemical reactions as described above may also be considered and can be easily simulated in non-directed experiments similar to the ones related to extraterrestrial ices evolution. Recently, it has been reported that irradiation of ice analogs using Circularly Polarized UV light on the DESIRS beamline on the synchrotron radiation facility SOLEIL in France, has produced a proteic amino acid, alanine, with a slight but significant enantiomeric excess, similar to the ones observed in some primitive chondrites from the solar nebula [31]. In the framework of a plausible astrophysical scenario, it is then proposed that a direct link between organic materials from primitive chondrites with photochemistry of interstellar ices exists, including a possible photochemistry step using some CPL whose existence in regions of high mass star formation regions is now documented [32].…”
Section: Relevance Of Organic Residues To the Problem Of Prebiotic Mamentioning
confidence: 72%
“…However, L-enantiomeric excesses (Lee) have been detected for some non-protein amino acids, such as α-methyl-α-amino acids, which have Lee of up to 18.5 % in Murchison, 6.0 % in Murray and 15.3 % in Orgueil Pizzarello et al 2003). Possible reasons for this excess include UV circularly polarized light (UV-CPL) in the presolar cloud (Bailey et al 1998;Bonner and Rubenstein 1987;Lucas et al 2005), a mechanism supported by laboratory simulations (de Marcellus et al 2011;Modica et al 2014), and/or solid-solution phase behaviour leading to the formation of conglomerate enantiopure solids during crystallization .…”
Section: Exogenous Sourcesmentioning
confidence: 90%
“…Here, 13 C-labelled achiral cosmic ice mixtures are irradiated with CPSR at beamline DESIRS (SOLEIL, France). In a previous measurement campaign, the irradiation experiments produced significant ees recorded for the amino acid alanine [8]. Multidimensional gas chromatography allowed us to determine an ee L of -1.3 % due to right-handed-CPL irradiation and +0.7 % due to left-handed-CPL irradiation.…”
Section: How Did Life Originate?mentioning
confidence: 95%